Transfer of Some Manuscripts from Ardabil, Ahiska, Bayezid and Erzurum to St. Petersburg in 1826-1829 - (:unkn) unknown (ISTANBUL UNIV, 2020)
While Russia seized Revan, Nakhchivan, Karabakh, Urmia and Ardabil between 1826-1828, they collected some manuscripts from the Iranian libraries and transferred them to Tbilisi and then to St. Petersburg. Some of those manuscripts were presented to the Czar of Russia in 1829 by Feth Ali Shah. During the War of 1828-1829 with the Ottomans, the Russians also collected some manuscripts from Turkish cities such as Ahiska, Erzurum and Bayezid. So far, there has been no study dealing with the fate of these manuscripts that were gathered from the aforementioned regions and then taken to St. Petersburg. There are catalogues of oriental manuscripts, but they do not contain any relevant information about these manuscripts. In other words, it does not provide information about who collected these manuscripts and how they changed hands. In this study, we will discuss the manuscripts that Russia collected from the Turkish-Islamic regions in the 1826-1829 War and brought to their capital based on Russian archive sources. Also information will be given on the current state of the manuscripts.
Keywords: 1828-1829 Ottoman Russian War; Iran; Manuscripts; Library; St. Petersburg